Improving Palliative Care Conversations Through Targeted Education and Mentorship. Issue 4 (August 2020) - Burgunder-Zdravkovski, Lorraine; Guzman, Yuri; Creech, Constance; Price, Deborah; Filter, Marilyn
Abstract : Health care provider communication proficiency is critical in the initiation and revisitation of these discussions throughout the trajectory of chronic illness. The delivery of palliative care (PC) throughout the continuum of illness has traditionally been underutilized. Nurses have the ability to significantly improve PC utilization through the use of advance care planning strategies to confidently initiate conversations with patients and families at multiple points throughout the continuum of illness. Nurses are uniquely positioned to contribute to the improvement of care provided to terminally and chronically ill patients because of the relationship developed and the knowledge of patient-specific disease progression that unfolds during the time spent with patients. In this study, nurses improved communication efficacy by learning to utilize advance care planning–specific interview strategies inclusive of scripting and cued language when initiating PC conversations. The preintervention/postintervention confidence levels of nurses in initiating early PC conversations significantly increased to improve the delivery of PC to patients.